Constitutive interaction between neutrophils and von Willebrand factor in peripheral blood - Yan Wan; Min Gao; Jueyi Zhu; Qingqing Mu; Yue Pan; Yifan Chen; Ting Yang; Wei Deng (Scientific Reports)
Abstract Neutrophils are known to be able to recruit von Willebrand factor (VWF) through Neutrophil Extracellular Traps (NETs) during inflammation. However, the interaction between neutrophils with plasma VWF at physiological condition remains poorly understood. In this study, we demonstrate that peripheral neutrophils constitutively carry surface-bound VWF in a NETs-independent manner. Depletion of peripheral neutrophils in mice elevated plasma VWF levels without affecting its synthesis or secretion. A similar interaction in human blood was also observed as demonstrated from the analysis of 23 healthy human donors. Human VWF binding to neutrophils is independent of gender and age; however, individuals with non-O blood types exhibit significantly lower VWF levels on neutrophils compared to those with type O blood. Furthermore, we found that the isolated human neutrophils bind stronger to the neuraminidase-treated VWF than untreated VWF. PSGL-1 and β2-integrins, two neutrophil membrane receptors, seemingly mediate this interaction since antibodies targeting both receptors showed a significant attenuating role here. These findings suggest a constitutive interaction between neutrophils and VWF in peripheral blood, in which the desialylation VWF seems play a major role here. Both PSGL-1 and β2-integrins receptors on neutrophil contribute to this interaction. Our study reveals a function of neutrophils beyond their established antimicrobial roles.